Product Copy Generation for Fashion Footwear Data - Baruah, Sudesna; V., Bagya Lakshmi (Indian Journal of Computer Science, 2021)
Natural Language Generation is a specialized field of Artificial Intelligence (AI) that deals with generation of text, given a set of inputs, like text, image or both. It is also deals with training of a given algorithm or machine to learn about a particular information and build relevant set of information about it in the form of natural language or text, given an input, while validating the same. This technology has stirred up a storm in the field of AI and has a great impact on automation science.